Optimal doping of gase crystals for nonlinear optics applications - Andreev, Yury M. 1946-; Vaitulevich, Elena A.; Kokh, Konstantin A.; Lanskii, Grigory V.; Losev, Valery F.; Lubenko, Dmitry M.; Svetlichnyi, Valerii A.; Soldatov, Anatoly N.; Shaiduko, Anna V. (Russian physics journal)
Centimeter-sized crystals of GaSe have been grown by a modified vertical Bridgman method from a melt with content 0.01, 0.05, 0.1, 0.2, 0.5, 1, and 2 at.% Al and 0.025, 0.1, 0.5, 1, and 2 at.% Er using heat field rotation. Their physical properties have been investigated and compared with the properties of doped crystals with content 0.1, 0.5, 1, 2, 3, 5, 7, and 10.2 mass% S, 0.01, 0.1, 0.5, 1, 2, 3, and 5 mass% In, and 0.01, 0.1, 0.5, 1, and 2 mass% Te, grown by the same method and by the conventional Bridgman method. Optimal levels of doping of GaSe crystals with Al and Er have been established here for the first time to be equal to 0.01- 0.05 at.% Al and ~0.5 at.% Er, respectively, of the growth charge.